GEOCHEMICAL FEATURES OF HYDROXY ACIDS IN SOIL SAMPLES FROM THE McMURDO DRY VALLEYS, ANTARCTICA - マツモト, ゲンキ; ワタヌキ, クニヒコ; トリイ, テツヤ; MATSUMOTO, Genki I.; WATANUKI, Kunihiko; TORII, Tetsuya (National Institute of Polar Research, 1990)
P(論文) Hydroxy acids in 12 soil samples from the Wright and Taylor Valleys of the McMurdo Dry Valleys (Ross Desert) in southern Victoria Land, Antarctica have been studied to clarify their features and to elucidate the source materials. A suite of 3-hydroxy (C_8-C_<30>) and (ω-1)-hydroxy (C_<22>-C_<30>) acids presenting the predominance of even-carbon numbers were found in the soil samples, while 2-hydroxy (C_8-C_<30>) and ω-hydroxy (C_8-C_<30>) acids showed no even-carbon predominance. These hydroxy acids are probably attributed to the degradation products of wind-transported cyanobacterial mats in and around streams, lakes and ponds, as well as to the past biological activity, involving bacteria, cyanobacteria and fungi, rather than originating from the Beacon Supergroup of Gondwanaland sediments and living organisms. departmental bulletin paper